PENERAPAN MODEL PEMBELAJARAN PETA PIKIRAN UNTUK MENINGKATKAN KETERAMPILAN MENULIS CERPEN SISWA SMK - Bunga, Jimiana (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2018)
AbstractThe backrond of this research is about the low of study result. The focus of this research is made short story text with mind map model. This model ia a way how to increase the students ability in short story in a good text. The method used in this research is qualitative-descripstive method. The subject of this research is Office Administration in SMK Negeri 3 Pontianak. The object research is the mind map model. The research instrument used is the test of study result in the form of short story text created by students which has been the validaty and reliabelity of test and also the observation sheet for observatioan the learning activity of the students and researcher. This can be seen from the data obtained in the first cycle planning of 91%, II 95% silkus, and the third cycle remains 95%. Implementation in the first cycle of 88%, the second cycle of 94% and the third cycle of 97%. Average learning outcomes also experienced an increase in the first cycle of 80,42, the second cycle of 82,52, and the third cycle of 94,78. Responsive aspects of cycle I to very good 3%, 50% cycle II, cycle III 50%. Â Keywords: short story text and mind map modelÂ